Analisis Makna Sosial Pada Tradisi Mufakat Kecik dan Mufakat Gedang di Desa Tunggang Kecamatan Pondok Suguh Kabupaten Mukomuko - Satria, Irwan; Meddyan Heriadi; Tini Afriani (LITERATUR: Jurnal Bahasa, Sastra dan Pengajaran, 2025)
This study aims to analyze the social meanings of the mufakat kecik and mufakat gedang traditions in Tunggang Village, Pondok Suguh District, Mukomuko Regency. The method used in this study is a qualitative method with a descriptive approach. Data were collected through observation, interviews, and documentation, focusing on the social meanings contained in the implementation of these traditions. The results show that the mufakat kecik and mufakat gedang traditions have existed since ancient times and are still practiced from generation to generation by the community of Tunggang Village, particularly as part of wedding ceremonies. These traditions play an important role as a form of respect for ancestors and as an effort to preserve local culture. The social meanings embedded in these traditions include strengthening social ties, mutual cooperation, mutual assistance, intergenerational communication, fostering solidarity, and instilling moral values. The conclusion of this study indicates that the mufakat kecik and mufakat gedang traditions possess strong social and cultural values and are considered sacred; therefore, their existence needs to be continuously maintained and preserved by the community.   Keywords: consensus, social meaning, tradition